The Effect of Organizational Commitment, Competence on Satisfaction and Performance of Lecturers at the Makassar South Sulawesi Maritime Polytechnic - Siti Zulaikah; Mulyadi Hamid; Sri Adrianti Muin (MediaTrend, 2022)
This study aims to determine and analyze the effect of commitment, competence on the satisfaction and performance of the lecturers of the Makassar South Sulawesi Shipping Science Polytechnic.The research approach used in this study is a quantitative method with an explanatory approach. From the total population data, the slovin formula was used to obtain a sample of 100 respondents.These results indicate that the path coefficient between the variables, namely job satisfaction has no positive and significant effect on lecturer performance, organizational commitment directly affects lecturer job satisfaction, organizational commitment has a positive and significant effect on lecturer performance, competence directly has a positive and significant effect on satisfaction work and competence did not have a positive and significant effect on the performance of lecturers at the Makassar South Sulawesi Shipping Polytechnic